2004
DOI: 10.1080/14756360400002072
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 5-lipoxygenase and Leukotriene C4Synthase in Human Blood Cells by Thymoquinone

Abstract: Black cumin seed, Nigella sativa L., and its oils have traditionally been used for the treatment of asthma and other inflammatory diseases. Thymoquinone (TQ) has been proposed to be one of the major active components of the drug. Since leukotrienes (LTs) are important mediators in asthma and inflammatory processes, the effects of TQ on leukotriene formation were studied in human blood cells. TQ provoked a significant concentration-dependent inhibition of both LTC4 and LTB4 formation from endogenous substrate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 13 publications
4
72
0
1
Order By: Relevance
“…Direct inhibition of 5-LO in cellfree assays was demonstrated for the ortho-quinone aethiopinone 79 from Salvia aethiopsis (L.) [150] and thymoquinone 77 [63] with IC 50 values of 0.11 and 3 mM, respectively, and both compounds suppressed 5-LO in activated leukocytes with comparable efficacies ( Table 5). More detailed analysis of thymoquinone's 77 action revealed that, in addition to 5-LO (IC 50 = 3 mM), it also blocks LTC 4 synthase activity, albeit less potently (IC 50 = 10 mM) [63], and aethiopinone 79 inhibited synovial PLA 2 (IC 50 = 10 mM), but had no effects on COX enzymes [150]. Some of the investigated quinones {e. g., thymoquinone 77, atracylochromene 80 and 2-[(2E)-3,7-dimethyl-2,6-octadienyl]-6-methyl-2,5-cyclohexadiene-1,4-dione 81} also inhibited COX-1 at about 10-or more-fold higher concentrations [53], [118], [148].…”
Section: Quinonesmentioning
confidence: 88%
See 3 more Smart Citations
“…Direct inhibition of 5-LO in cellfree assays was demonstrated for the ortho-quinone aethiopinone 79 from Salvia aethiopsis (L.) [150] and thymoquinone 77 [63] with IC 50 values of 0.11 and 3 mM, respectively, and both compounds suppressed 5-LO in activated leukocytes with comparable efficacies ( Table 5). More detailed analysis of thymoquinone's 77 action revealed that, in addition to 5-LO (IC 50 = 3 mM), it also blocks LTC 4 synthase activity, albeit less potently (IC 50 = 10 mM) [63], and aethiopinone 79 inhibited synovial PLA 2 (IC 50 = 10 mM), but had no effects on COX enzymes [150]. Some of the investigated quinones {e. g., thymoquinone 77, atracylochromene 80 and 2-[(2E)-3,7-dimethyl-2,6-octadienyl]-6-methyl-2,5-cyclohexadiene-1,4-dione 81} also inhibited COX-1 at about 10-or more-fold higher concentrations [53], [118], [148].…”
Section: Quinonesmentioning
confidence: 88%
“…[53], [118] might be superior, at least in intact cells (IC 50 = 0.2 ± 7.5 mM, see Table 5). Thymoquinone 77 and its polymer nigellone 78 from Nigella sativa (L.) that lack pronounced lipophilic residues are quite efficient as well [63], [148], [149]. Direct inhibition of 5-LO in cellfree assays was demonstrated for the ortho-quinone aethiopinone 79 from Salvia aethiopsis (L.) [150] and thymoquinone 77 [63] with IC 50 values of 0.11 and 3 mM, respectively, and both compounds suppressed 5-LO in activated leukocytes with comparable efficacies ( Table 5).…”
Section: Quinonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Prednisolone which is used in group I, produces bronchial muscle relaxation indirectly through inhibiting the release of LTs and reversing mucosal edema. [11] In group II with chamomile, significant is poor when given by inhalation. No real improvement occurs in asthmatic symptoms in spite of its relaxant effect on rabbit tracheal muscle contraction when given by inhalation.…”
Section: Discussionmentioning
confidence: 99%